2017
DOI: 10.4238/gmr16019102
|View full text |Cite
|
Sign up to set email alerts
|

A large-scale analysis study on the clinical and viral characteristics of hepatitis B infection with concurrence of hepatitis B surface or E antigens and their corresponding antibodies

Abstract: ABSTRACT. Concurrent detection of hepatitis B surface antigen (HBsAg) and anti-HBs antibody or hepatitis B surface E antigen (HBeAg) and anti-HBe antibody in patients with chronic hepatitis B (CHB) infection is well established. However, the clinical implications of these proteins remain largely unknown. In this study, demographic, clinical, and laboratory data from 124,865 patients with chronic CHB infection were analyzed. Viral genotypes were determined by nested polymerase chain reaction. A chemiluminescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
3
11
1
Order By: Relevance
“…A small numbers of the study cohort showed co-existence of HBs Ag/Hbs Ab reactive probably on a transitional state to clear the virus or probably suggesting a selection of immune escape mutants during the disease period, a finding previously reported. 32,[34][35][36][37] Individuals with immune tolerance CHBV could not be identified within the study cohort, in agreement with recent reports that challenged the early concepts of existence of this immune pathologic phase. Recent evidence showed that subtle liver damage in the presence of normal aminotransferases levels exits in CHBV individuals.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A small numbers of the study cohort showed co-existence of HBs Ag/Hbs Ab reactive probably on a transitional state to clear the virus or probably suggesting a selection of immune escape mutants during the disease period, a finding previously reported. 32,[34][35][36][37] Individuals with immune tolerance CHBV could not be identified within the study cohort, in agreement with recent reports that challenged the early concepts of existence of this immune pathologic phase. Recent evidence showed that subtle liver damage in the presence of normal aminotransferases levels exits in CHBV individuals.…”
Section: Discussionsupporting
confidence: 85%
“…33 Cheng and colleagues 34 reported that the majority of their patients were Hbs Ag/HBe Ag/Hbc Ag reactive, a finding that is discordant with our findings. 34 Hbe Ag/HBe Ab non-reactivity was seen in the majority of our cohort, this probably indicates disease inactivity or immune exhaustion that has been well-documented in CHBV. Furthermore, Hbe Ag/HBe Ab non-reactivity could mean mutations in the pre-core or core regions of the viral genome.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Hepatitis B e antigen (HBeAg) is a critical indicator to determine the severity of the disease and it is associated with the activity of viral replication and infectivity (22). In addition, HBeAg analysis is useful for predicting seroconversion and disease progression (23).…”
Section: Factors Associated With Disease Progression and Viral Replicmentioning
confidence: 99%
“…The host immune response causes both hepatocellular damage and clearance of viral antigen [46]. Serum markers of HBV infection might help with assessment of various issues such as prognosis [79].…”
Section: Introductionmentioning
confidence: 99%